THE IMPLEMENTATION OF VIRTUAL MACHINE SIMULATION METHODS ON LEARNING THE OPERATION SYSTEM INSTALLATION IN STATE VOCATIONAL HIGH SCHOOL 5 MAKASSAR - - Nurdiana; Hasdar Hanafi; Nina Ikhwati Wahidah (International Journal of Education, Information Technology, and Others, 2018)
The purposes of this research are to investigate: (1) the process of using virtual machine simulation method in operation system installation learning, (2) the differences of students’ learning outcomes between the ones using Virtual Machine simulation method and the ones using conventional method, and (3) the effectiveness of using Virtual Machine simulation method in operation system installation learning. This research is a Quasi Experiment research. The research design employed Pretest-Posttest Control Design with 60 subjects as the samples of the research. Data was collected by employing of students’ learning outcomes. Data was analyzed by using descriptive and parametric inferential statistic with independent sample t-test analysis. The results of the research show that: (1) the Process of using Virtual Machine simulation method in operating system installation learning are the material preparation phase and implementation phase which consisted of several activities, namely installing Virtual Machine and operational system, (2) There are differences of students’ learning outcomes where the experimental class is higher than the control class, and (3) the Virtual Machine simulation method in operation system installation learning is more effective than the direct method.